Colliding Terminological Systems—Immanuel Kant and Contemporary Empirical Aesthetics. (July 2019) - Hayn-Leichsenring, Gregor U.; Chatterjee, Anjan
Few classic philosophers are as popular as Immanuel Kant. Kant's ideas seem to be used ubiquitously in contemporary aesthetics discussions. Here, we critically review the way his ideas are being applied in empirical research. We focus on the four moments presented in the Critique of the Power of Judgment (first published in 1790) and show that Kant's precise (and sometimes counter-intuitive) use of language paired with his complex transcendental framework make interpretation of his work difficult. In some cases, colliding terminological systems easily lead to misinterpretations of his ideas. Further complicating matters, Kant developed a coherent and static description of judgments on the beautiful, while modern empiricists conduct experiments to construct a dynamic explanation of aesthetic experiences. These two approaches are difficult to reconcile. We outline points of tension and also areas where his ideas relate to and might motivate productive research questions.